Employer Power and Employment in Developing Countries - Nancy H. Chau; Ravi Kanbur; Vidhya Soundararajan (Institute of Labor Economics (IZA), 2022)
The issue of employer power is underemphasized in the development literature. The default model is usually one of competitive labor markets. This assumption matters for analysis and policy prescription. There is growing evidence that the competitive labor markets assump- tion is not valid for developing countries. Our objective in this paper is to review this evidence, to present theoretical and policy perspectives which follow from it, and to highlight areas for further research.
Keywords: J42; O15; 330; employer power; employment; developing countries